Editing an α-globin enhancer in primary human hematopoietic stem cells as a treatment for β-thalassemia - Mettananda, Sachith; Fisher, Chris A.; Hay, Deborah; Badat, Mohsin; Quek, Lynn; Clark, Kevin; Hublitz, Philip; Downes, Damien; Kerry, Jon; Gosden, Matthew; Telenius, Jelena; Sloane-Stanley, Jackie A.; et al. (Nature communications, 2017)
β-Thalassemia is one of the most common inherited anemias, with no effective cure for most patients. The pathophysiology reflects an imbalance between α- and β-globin chains with an excess of free α-globin chains causing ineffective erythropoiesis and hemolysis. When α-thalassemia is co-inherited with β-thalassemia, excess free α-globin chains are reduced significantly ameliorating the clinical severity. Here we demonstrate the use of CRISPR/Cas9 genome editing of primary human hematopoietic stem/progenitor (CD34+) cells to emulate a natural mutation, which deletes the MCS-R2 α-globin enhancer and causes α-thalassemia. When edited CD34+ cells are differentiated into erythroid cells, we observe the expected reduction in α-globin expression and a correction of the pathologic globin chain imbalance in cells from patients with β-thalassemia. Xenograft assays show that a proportion of the edited CD34+ cells are long-term repopulating hematopoietic stem cells, demonstrating the potential of this approach for translation into a therapy for β-thalassemia. β-thalassemia is characterised by the presence of an excess of α-globin chains, which contribute to erythrocyte pathology. Here the authors use CRISP/Cas9 to reduce α-globin expression in hematopoietic precursors, and show effectiveness in xenograft assays in mice.